Pharmaceutical care in the misuse of drugs for weight loss: systematic review (Research, Society and Development, 2023)
Introduction: The high search for short-term weight loss leads to the misuse of weight loss drugs without the supervision of a health professional, which can cause physical dependence, intoxication and serious side effects. Objective: To present the forms of intervention by the pharmacist in the misuse of weight loss drugs. Methodology: This is a systematic review following Prisma criteria, using the database of online virtual libraries BVS, Scielo and Pubmed. Inclusion criteria are: publications of articles in the last 10 years (2012-2022) that are available in Portuguese and English in the informed databases, easily accessible articles on appetite suppressants. Results: The main effects reported in the use of these drugs are: dehydration, chronic diarrhea and constipation, metabolic acidosis, hypokalemia, cardiac arrhythmia; hemorrhagic and ischemic stroke; renal and hepatic failure. The main pharmacological indication for obesity is for those who have profiles with more serious consequences, such as hypertension, diabetes, among other comorbidities who have not been successful in losing weight only with changes in lifestyle. Pharmacists are directly involved in dispensing weight loss products, providing useful information about their use and their main adverse effects. Conclusions: It is essential that the patient seeks professional guidance before starting the use of weight loss drugs, so that they are aware of the contraindications, side effects and that the administration of these drugs is done correctly.